A methods engineering study on Metro Ice Cream - Baquiran, Francis Allan; Omictin, Michael Philip Enriquez; Po, Ronald Aaron Uy. (Diliman, Quezon City College of Engineering, 2001)
This study aims to apply concepts and techniques learned in IE 32 : Methods Engineering in a real life production system, particularly that of an ice cream manufacturer. Metro Ice Cream, a small-scale ice cream manufacturer in Quezon City, was the chosen site. The study concentrated on processes that affect product freshness and quality. Improvement of the company's storage system is another objective of this study. The current system was documented. This includes company profile, product and process documentation, facility layout, production systems framework, catalog of equipment, manpower documentation and working conditions. Problems were identified and analyzed using streamline diagnosis chart, Ishikawa diagram and root cause verification matrix. The four main problems that were identified were the disorderly freezer, difficulty in transporting materials, the FIFO policy not being strictly followed and the layout design allows too much walking distances between processes. Alternatives were identified for each problem and these alternatives were evaluated using Kepner-Tregoe's Decision Analysis. Among the recommendations initiated by this study are a new facility layout, a new freezer layout, carts, color coding schemes and ID's for the storage system and the installation of a mechanical elevator.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering.
Keywords: Systems analysis